The Impact of Tik-Tok Use on Self-Expression by Generation-Z users - Eryc Eryc (Sekolah Tinggi Manajemen Informatika dan Komputer Jayakarta, 2022)
This research aims to find out the self-expression of Tik-Tok Generation Z users, namely young people in the 1city of Batam. Tik-Tok is a social media platform that allows users to express themselves with short videos on social media, satisfying the need for expression and other motives among generation Z. The motive found can be a study for further development for social media developers from the data presented. In research using a qualitative approach by conducting focus group discussions with three different age ranges from Generation Z and interviews. Through knowing the motive, amatic analysis will be conducted based on the motive to determine the needs of Generation Z satisfied, and in-depth interviews will be conducted to obtain in-depth data. The results are based on the motivations of Tik-Tok Generation Z users through time, friendship, escapism, enjoyment, social interaction, relaxation, information, and expression. Many users have produced popular content on the Tik-Tok app with short videos to satisfy their needs and build connections. The conclusions of this study show that different age ranges of Generation-Z have different motivations in using Tik-Tok and by meeting their needs, they become active users in using a part of their lives and expressing themselves on the platform.